Seed viability of feathertop Rhodes grass (Chloris virgata Sw.) reduced by silage, digestion, and sheep rumen digestion - Asaduzzaman, Md; Piltz, John; Koetz, Eric; Hopwood, Michael; Shephard, Adam; Wu, Hanwen (Frontiers in Agronomy, 2022)
Weed seeds can be spread by different vectors and seed dispersal is an important mechanism for the weed to persist. Weed seeds passaging through the digestive tract of a ruminant animal is expected to result in reduced viability. Two separate experiments were conducted to determine the germinability and viability of mature seeds of feathertop Rhodes grass (Chloris virgata Sw.) after exposure to four treatments, i.e three-months in silage, 48-hours in the rumen of steers, silage plus digestion and passing through the digestive tract of sheep. Our results showed that three different treatments (silage, digestion and silage + digestion) can inhibit 90% to 100% of the seed germination of feathertop Rhodes grass. Both silage and digestion reduced seed viability by 65%-90% depending on the population. Silage followed by digestion reduced viability by 80% - 97%. The sheep feeding study showed that total viable seeds from the daily recovery of faeces for 12 consecutive days after ingestion was only 0.084% and 0.022% in the 2020 and 2021 experiments respectively. In comparison with the untreated control, seed viability of feathertop Rhodes grass was reduced by more than 99.9% after feeding through sheep, indicating the spreading of feathertop Rhodes grass seeds via sheep faeces is minimal. These results indicate that silage, digestion, silage followed by digestion, and ingestion of mature seeds are effective non-chemical weed management options for an integrated weed management package for feathertop Rhodes grass.